Vertebral cardiac index determination in mongrel dogs - Castillo, Edy (2020)
The investigation objective was to determine the vertebral cardiac index (VCI) in mongrel dogs, from Cuenca city at 2560 meters above sea level and compare it with the results of different studies carried out with different conditions and altitudes. The heart´s size was evaluated by Buchanan and Bucheler method (1995), that relate the height and width of the heart, with a specific number and position of thoracic vertebrae in Beagle dogs. For this descriptive study there were selected thirty-three clinically healthy mongrel dogs, without discrimination of sex, and an age range from one to five years. The animals were clinical tested and after that a radiographic examination of the thorax with a right lateral projection was made. The vertebral cardiac index values obtained, showed a normal distribution, with an average of 9.38 vertebrae and a standard deviation of ± 0.7. The minimum value found was equal to 8.8 vertebrae and the maximum was equal to 9.8 vertebrae. The confidence analysis of the VCI verifies that the general range VCI measure is not influenced by weight, age or sex; and can be standardized in mongrel dogs that live in this conditions.